2019
DOI: 10.1177/1941738119849112
|View full text |Cite
|
Sign up to set email alerts
|

Injury in Brazilian Jiu-Jitsu Training

Abstract: Background: Brazilian jiu-jitsu (BJJ) is a grappling-based martial art that can lead to injuries both in training and in competition. There is a paucity of data regarding injuries sustained while training in BJJ, in both competitive and noncompetitive jiu-jitsu athletes. Hypothesis: We hypothesize that most BJJ practitioners sustain injuries to various body locations while in training and in competition. Our primary objective was to describe injuries sustained while training for BJJ, both in practice and in co… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

3
38
0
16

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 32 publications
(57 citation statements)
references
References 13 publications
3
38
0
16
Order By: Relevance
“…When comparing jiu-jitsu with other fighting modalities, a study addressing injuries caused by judo found chirodactyls and knees to be the most common affected sites, similar to our findings. 19 Petrisor et al 4 conducted a questionnaire-based study with 70 jiu-jitsu practitioners to establish the epidemiology of injuries suffered in the sport. In line with our findings, they reported 91% of injuries to occur during training and a high prevalence of injuries in the neck, fingers/hand, knees, shoulders, and elbows.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…When comparing jiu-jitsu with other fighting modalities, a study addressing injuries caused by judo found chirodactyls and knees to be the most common affected sites, similar to our findings. 19 Petrisor et al 4 conducted a questionnaire-based study with 70 jiu-jitsu practitioners to establish the epidemiology of injuries suffered in the sport. In line with our findings, they reported 91% of injuries to occur during training and a high prevalence of injuries in the neck, fingers/hand, knees, shoulders, and elbows.…”
Section: Discussionmentioning
confidence: 99%
“…In jiu-jitsu, the goal is to finish the fight using projections, chokes, twists, and immobilizations, often with joint blockage, which may result in various types of lesions, predominantly orthopedic. [1][2][3][4][5] These fights are characterized by unexpected, fast, repetitive, and high-intensity effort movements, subjecting joints and muscles to an intense overload. Added to the large number of competitions and training intensity, these factors incur in many musculoskeletal injuries.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Studies on injuries in BJJ found that only 6% of injuries happen during contests [13] and that these are usually orthopaedic injuries [7] affecting mainly knees and elbows [8]. Most injuries happen during training [13] and they usually affect distal limb parts, i.e. hands, feet, ngers and toes [9].…”
Section: Discussionmentioning
confidence: 99%
“…The injuries affect the limbs as well as the torso, and internal organs [9][10][11][12]. It has been found that athletes sustain more injuries during training than during competitions [13].…”
Section: Introductionmentioning
confidence: 99%